Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa Kelas IV Pembelajaran IPA Tema 1 Subtema 1 SDN 122398 Pematang Siantar - Irfan Siagian; Lisbet Novianti Sihombing; Canni Loren Sianturi (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine: The influence of the Problem Based Learning Model on the Learning Outcomes of Class IV Students in Science Learning Theme 1 Subtheme 1 at SDN 122398 Pematang Siantar. The type of research used in this research is Quantitative Research, which states that quantitative research is research in the form of numbers and analysis using statistics. The research design that will be used is an experiment, in the form of Pre-Experimental Design which uses a